SHOWING THE GOODNESS OF ARTIFICIAL NEURAL NETWORK MODEL FROM THE STATISTICAL MODEL - Jasim, Saleema (Iraqi Journal of Science, 2024)
The aim of this research , Principal component Is to find orthognal sets of vectors that maximize the variance of the projected dat, pca seeks a transformation nation of the data into another from of reference with as little error as possible, using fewer factors than the original datat. and find the connection among the student’s degrees through an applicative study on accountancy department for the afternoon studied who graduated in 2002- 2003 in Management and Economy- Baghdad University.After taking their marks for the last year downward to the third year , second and first year far of the fail years with using of the model of artificial neural network and the statistical model (principle component), to compared the results between the two models and show the goodness of the artificial neural network as a method could be reliable instead of the statistical model